2014
DOI: 10.1175/waf-d-12-00123.1
|View full text |Cite
|
Sign up to set email alerts
|

Assimilating MTSAT-Derived Humidity in Nowcasting Sea Fog over the Yellow Sea

Abstract: An extended three-dimensional variational data assimilation (3DVAR) method based on the Weather Research and Forecasting Model (WRF) is developed to assimilate satellite-derived humidity from sea fog at its initial stage over the Yellow Sea. The sea fog properties, including its horizontal distribution and thickness, are retrieved empirically from the infrared and visible cloud imageries of the Multifunctional Transport Satellite (MTSAT). Assuming a relative humidity of 100% in fog, the MTSAT-derived humidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 44 publications
0
70
0
Order By: Relevance
“…Only the mechanism of gravitational settling is considered for a smooth surface, for instance, bare soil and ocean when calculating deposition velocity (Katata et al, ). A threshold of 0.016 g kg −1 for LWC is generally adopted to diagnose simulated sea fog (e.g., Gao et al, ; Wang et al, ; Yang et al, ; Zhou & Du, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only the mechanism of gravitational settling is considered for a smooth surface, for instance, bare soil and ocean when calculating deposition velocity (Katata et al, ). A threshold of 0.016 g kg −1 for LWC is generally adopted to diagnose simulated sea fog (e.g., Gao et al, ; Wang et al, ; Yang et al, ; Zhou & Du, ).…”
Section: Methodsmentioning
confidence: 99%
“…The statistical scores shown in Table quantitatively evaluate the last 24‐hr simulation of sea fog area. The values are obtained using the objective evaluation method widely used in previous sea fog numerical studies (e.g., Gao et al, ; Wang et al, ; Yang et al, ; Zhou & Du, ). The results show that Exp‐TOP has a smaller false alarm ratio (FAR; 0.423 versus 0.473) and a bias value (Bias) closer to 1.0 (0.968 versus 1.179) than Exp‐noTOP.…”
Section: Improvements Of Sea Fog Simulation Caused By the Top‐driven mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, DA studies on fog prediction have examined the roles of both techniques and observations. With regard to DA techniques, the potential of 1D variational (1DVAR; Bergot et al 2005;Muller et al 2007) and 3D variational (3DVAR; Gao et al 2010;Wang et al 2014) data assimilation, as well as more-advanced techniques such as 4D variational data assimilation (4DVAR; Vandenberghe and Ware 2003) and the ensemble Kalman filter (EnKF; Remy and Bergot 2010), has been explored and promising results have been obtained. The results showed that fog forecasting was greatly improved as a result of improvement of model initial conditions after DA.…”
Section: Introductionmentioning
confidence: 99%